No road leading back : an improbable escape from the Nazis and the tangled way we tell the story of the Holocaust - Heath, Chris (Schocken Books, 2024)
"This by turns shattering and hope-giving account of prisoners who dug their way out of torture and bondage by the Nazis is both a stunning escape narrative and an object lesson in how we remember and continually forget the particulars of the Holocaust. No Road Leading Back is the remarkable story of a dozen prisoners who escaped from the pits where more than 70,000 Jews were shot in the Lithuanian forest after the Nazi invasion of Eastern Europe in 1941, and where they were forced participants in the equally horrific aftermath: anxious to hide the incriminating evidence of the murders, the S.S. enslaved a group of Jews to exhume every one of the bodies and incinerate them all in a months-long labor-an episode whose specifics are staggering and disturbing, even within the context of the Holocaust. From within that dire circumstance emerges the improbable escape made by some of the men who were part of this "burning brigade." They dug a tunnel with bare hands and spoons while they were trapped and guarded day and night-an act not just of great bravery and desperation but of awesome imagination. Based on first-person accounts of the escapees and on each scrap of evidence that has been documented, repressed, or amplified since, this book resurrects their lives and their acts of witness, as well as providing a complex, urgent analysis of why their story has rarely been told, and never accurately. Heath explores the cultural use and misuse of Holocaust testimony and the need for us to face it-and all uncomfortable historical truths-with honesty and accuracy"--